2019
DOI: 10.3390/rs11050488
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variations in Chlorophyll Fluorescence Associated with Photosynthesis at Leaf and Canopy Scales

Abstract: There is a critical need for sensitive remote sensing approaches to monitor the parameters governing photosynthesis, at the temporal scales relevant to their natural dynamics. The photochemical reflectance index (PRI) and chlorophyll fluorescence (F) offer a strong potential for monitoring photosynthesis at local, regional, and global scales, however the relationships between photosynthesis and solar induced F (SIF) on diurnal and seasonal scales are not fully understood. This study examines how the fine spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 60 publications
5
53
1
Order By: Relevance
“…Sites with sparse vegetation (e.g., shrubland systems) appeared to not as consistently have the same diurnal shape ( Figure S9). This could potentially be due to the low leaf area index (LAI) in shrublands contributing to a higher influence from the background soil, which has been found to decrease the midday NDVI values [27] and is shown in supplementary Figure S9. Campbell et al [27] found, however, that this decrease in midday NDVI values did not occur for areas with higher LAI values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sites with sparse vegetation (e.g., shrubland systems) appeared to not as consistently have the same diurnal shape ( Figure S9). This could potentially be due to the low leaf area index (LAI) in shrublands contributing to a higher influence from the background soil, which has been found to decrease the midday NDVI values [27] and is shown in supplementary Figure S9. Campbell et al [27] found, however, that this decrease in midday NDVI values did not occur for areas with higher LAI values.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially be due to the low leaf area index (LAI) in shrublands contributing to a higher influence from the background soil, which has been found to decrease the midday NDVI values [27] and is shown in supplementary Figure S9. Campbell et al [27] found, however, that this decrease in midday NDVI values did not occur for areas with higher LAI values. NDVI values at shrubland sites appear to be less noisy due to having characteristically less clouds and precipitation and a more comprehensive statistical framework, like the one presented here, might not be as necessary, though further work needs to be done on this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The F INT ranges between an average value of 14 mW m −2 sr −1 up to more than 250 mW m −2 sr −1 nm −1 when the canopy is mature. The overall evolution of F across the growing season primarily responds to the illumination level and to the amount of green biomass in the canopy, especially to the chlorophyll content during the different growing stages [14,53,60]. The average value of downwelling radiance computed in the 400-700 nm spectral windows shows an increasing trend, related to changes in solar zenith angle across the season (from February to May).…”
Section: 2f Spectrum From Experimental Field Spectroscopymentioning
confidence: 99%
“…Joiner et al, (2016) [10] and Wolanin et al, (2015) [11] were the only attempts to retrieve red F from GOSAT and SCIAMACHY, respectively. Conversely, studies based on measurements collected by field spectrometers [12][13][14][15][16] and airborne high-resolution imaging spectroscopy [17][18][19][20][21][22] more frequently considered both the red and far-red F.…”
Section: Introductionmentioning
confidence: 99%